Altitude training as a means to improve sea level performance in elite level sprint kayakers - Andersson, R. D. (Journal of Australian Strength and Conditioning, 2017)
This case study investigated the effects of a pre-competition training camp at a moderate natural altitude on 4 elite level sprint kayakers. The kayakers spent 21 nights living at 1800m and training at varying heights between 915m and 2200m. The application of natural moderate altitude before competition improved Total Haemoglobin mass (tHb) 5.85% (SD ± 2.33), VO2 max 5.3% (SD ± 2.05), 4 min kayak ergometer performance 3.2% (SD ± 1.4), 30 sec kayak ergometer performance 2.7% (SD ± 2.51) and 45 sec kayak ergometer 1.5% (SD ± 0.92), skinfolds reduced 8.8% (SD ± 2.27). Competition performance is difficult to compare due to sprint kayaking being an outdoor sport that can be significantly affected by various environmental conditions (wind direction and speed, water temperature and viscosity). However, the results of this study demonstrate that elite sprint kayakers may benefit from moderate natural altitude exposure prior to sea-level performance.